Design of Automatic Goods Sorting Tool Based on Arduino Mega Based Paint Color Using TCS 3200 Sensor with IoT Monitoring - ilham, muhammad ilham pratama; Notosudjono, Didik; Machdi, Agustini Rodiah; Yunus, Mochamad (Journal of Energy and Electrical Engineering, 2024)
Technology in the industrial world is developing and being used very quickly. A shift from traditional machines and tools to modern machines and tools that are controlled automatically. Most of the sorting of goods in industry is still done manually by human workers, so automatic work control tools are needed for sorting. Sorting can be done by machine, manually, or with a bar code system. Based on several models, research on automatic item and color sorting has the same working principle. The additions made to these two references, namely adding the Internet of Things to monitor the number of objects and colors entering the sorting area or final holding container for color objects, lead to the connection method used in the tool with the addition of the Internet of Things system.